Evaluation of the Use of Cassava Based Complete Ration Silage on Nitrogen Retention and Metabolizable Energy Male Duck - Sofia Sandi; Asep Sudarman; Erika B Laconi; Komang G Wiryawan; Djumali Mangunwijaja (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The purpose of this study was to evaluate the effect of a complete ration silage made of cassava biomass nitrogen retention, and metabolizable energy male ducks. Control diet consisted of corn, rice bran, coconut meal, soybean meal, vegetable oil, fish meal and premix. While the treatment of silage ration of cassava based (BBS) consisted of leaves, peel, and tubers of cassava, as well as a mix of fish meal, vegetable oil, premix, DL-methionine and L-lysine. The experimental design used was completely randomized design with 5 treatments and 4 replicates ie S0 (100% control diet), S25 (75% control diet + 25% BBS silage), S50 (50% control diet + 50% BBS silage), S75 (25% control diet + 75% BBS silage), and S100 (100% BBS silage ration). Measurement of metabolizable energy and nitrogen retention was conducted using 25 male ducks aged 10 weeks maintained in metabolic cages and adapted to experimental diets for seven days. Ducks were fasted for 24 hours before the experimental diets were offered. Metabolizable energy and nitrogen retention were measured by the method of Sibbald (1989). The results showed that a decline in nitrogen retention and, metabolizable energy along with the increasing level of BBS silage in the rations. The conclusion of this study was the use of up to 75% BBS silage generated metabolizable energy and nitrogen retention that do not differ from the control ration.Key words: cassava silage, complete ration, male duck, metabolizable energy, nitrogen retention